Analysis of crack propagation in an adhesive joint / M.D. Mohan Gift, J. Selvakumar, S. John Alexis - M.D., Mohan Gift; J., Selvakumar; S., John Alexis (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
Adhesive joints are widely used in industries because they have several advantages when compared to welded and riveted joints. One of the important factors is that they distribute the load and stresses uniformly over the entire bonded area providing good vibration resistance. Adhesive joints can readily bond dissimilar materials. The prediction of crack propagation validating the adhesive joint durability and toughness is a significant point which is addressed through various experimental methodologies based on the type of loading conditions. The analysis is hindered by the unpredictable substrate and adhesive behavior due to the loading conditions, the nature of crack propagation, and the geometry. The impact of hardener resin ratio alteration is a parameter which needs to be explored in validating the joint toughness. The Double Cantilever Beam tests which are used for analyzing the fracture toughness for mode-1 loading in adhesive joints focus on adhesive thickness variation extensively. The alteration of composition and its role in influencing the crack propagation is explored in a limited perspective. An attempt is made in this work to analyse the adhesive composition variation and its impact on the joint toughness with the help of a DCB test involving three specimens incorporating variations in the hardener resin composition. The analytical and the experimental results provided significant insights on the adhesive joint toughness validation.